Exploration of students' algebraic thinking skills in solving TIMSS problems in terms of reflective-impulsive cognitive style - Pratama, Deni; Masduki, Masduki (Prima: Jurnal Pendidikan Matematika, 2024)
The algebraic thinking is very important for students to be able to abstract and generalize a mathematical problem. The purpose of this research is to reveal students' algebraic thinking processes in solving math problems based on reflective-impulsive cognitive styles. The method used is a qualitative with a case study approach. The research subjects consisted of 55 students who were then selected six students based on the reflective-impulsive cognitive style. The research instrument used consisted of an algebraic thinking test that adopted from TIMSS (Trends in International Mathematics and Science Study), MFFT (Matching Familiar Figure Test) and an interview guide. In this paper, researchers are focus on the exploration of students' algebraic thinking ability in solving problems on generalization and abstraction components. The finding showed that the reflective subjects and impulsive subjects are able to solve generalization and abstraction problems. The reflective and impulsive subjects are able to use patterns to solve problems related to generalizations. In addition, reflective and impulsive subjects are able to use symbols as an abstraction of the relationship between concepts and mathematical properties. However, the reflective subjects used the solution problem steps more systematic than impulsive subjects. The implication of the finding is that the individual differences such as cognitive style should be facilitated by the teachers so that students are more successful in learning mathematics.